The Use of Immunochemical Fecal Occult Blood Test as Colorectal Cancer Screening Tool in Asymptomatic Population in Indonesia - Murdani Abdullah; Hayatun Nufus; Ari Fahrial Syam; Dadang Makmun; Marcellus Simadibrata; Abdul Aziz Rani (The Indonesian Society for Digestive Endoscopy, 2014)
Background: Colorectal cancer is the fourth leading cause of cancer-related mortality worldwide. Earlydetection of colorectal cancer is necessary in term of increasing survival. Immunochemical fecal occult bloodtest (I-FOBT) is one of the simple and inexpensive screening modality that can be used widely. No data has been available yet regarding the usage of I-FOBT in Indonesia. This study is a prevalence study of I-FOBT in asymptomatic population in Indonesia. Method: A cross sectional study was conducted in asymptomatic population visiting five public health service centers in Depok district, West Java, Indonesia. This study was performed from January to March 2012. Casereport form and I-FOBT kit were used to assess and screen the patients. Statistic analysis was performed usingChi-square test. Results: The prevalence of positive I-FOBT was almost equally distributed among age group. Femaledominated whole patients 202 (72.7%). Most of them had middle to low education level 116 (41.7%). As manyas 50.7% patients had normal body mass index. We had 11 (4%) patients with positive result of I-FOBT. Conclusion: Prevalence of positive result of I-FOBT in asymptomatic population in Indonesia was 4%.Further studies were needed to confirm sensitivity and specifity of I-FOBT in Indonesia.Keywords: colorectal cancer, immunochemical fecal occult blood test (I-FOBT), early detection